31 Days Before Your CCNA Exam : a Day-by-Day Review Guide for the CCNA 640-802 Exam, Second Edition - Johnson, Allan (Cisco Press, 2008)
31 Days Before your CCNA Exam, Second Edition, offers you a personable and practical way to understand the certification process, commit to taking the exam, and finish your preparation using a variety of Foundational and Supplemental study resources. The book breaks down key exam topics into 31 daily review sessions using short summaries, lists, tables, examples, and graphics. A Study Resources section provides you with a quick reference for locating more in-depth treatment of a day's topics within the relevant Foundational and Supplemental resources. Use this day-by-day guide to organize, prepare, and review all the CCNA® objectives. The features of the book empower you to fit exam preparation into an otherwise busy schedule: Tear out visual calendar summarizes each day's study topics Checklist highlights important tasks and deadlines leading up to your exam Description of the 640-802 CCNA exam organization and sign up process, includes how to use a voucher Strategies from the author help you to be mentally, organizationally, and physically prepared for exam day Conversational tone, making your study time more enjoyable Allan Johnson entered the academic world in 1999 after ten years as a business owner and operator. He has a passion for teaching and holds both an MBA and an M. Ed in occupational training and development. Allan currently works full time developing CCNA instructional support and training materials.